2012
DOI: 10.1038/nrg3160
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of cytoplasmic mRNA decay

Abstract: Discoveries made over the past 20 years highlight the importance of mRNA decay as a means to modulate gene expression and thereby protein production. Up until recently, studies focused largely on identifying cis-acting sequences that serve as mRNA stability or instability elements, the proteins that bind these elements, how the process of translation influences mRNA decay, and the ribonucleases that catalyze decay. Now, current studies have begun to elucidate how the decay process is regulated. This review exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
574
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 550 publications
(608 citation statements)
references
References 119 publications
11
574
0
2
Order By: Relevance
“…It is known that phosphorylation regulates the binding and function of RNA-Bps (12). For example, TTP phosphorylation by MK2 downstream of p38 MAPK signaling facilitates TTP to degrade mRNA through inhibition of deadenylase (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that phosphorylation regulates the binding and function of RNA-Bps (12). For example, TTP phosphorylation by MK2 downstream of p38 MAPK signaling facilitates TTP to degrade mRNA through inhibition of deadenylase (28).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the activity of RNA-Bps is regulated by the activation of mitogen-activated protein kinases (MAPKs), such as p38 MAPK downstream of various stimuli, including IL-1β and lipopolysaccharide (LPS) (11,12). The regulation of cytokine mRNA stability by RNA-Bps is particularly important because of their essential roles (such as for IL-6) in human disease.…”
mentioning
confidence: 99%
“…This includes nanoparticlebased bio-barcode assay that detects protein and DNA with ultrahigh sensitivity [11][12][13][14][15] , and although shown highly sensitive and versatile, this method is yet to be widely used partly because of the use of a non-conventional light-scattering assay platform. Further, it is very difficult to reliably and sensitively detect 19-to 25-nucleotide-long miRNA targets because miRNA is easily degradable by RNase 16 . In this regard, the bio-barcode approach that detects a barcode DNA that is a surrogate for a miRNA target could be beneficial.…”
mentioning
confidence: 99%
“…It has long been thought that nonsense-mediated mRNA decay (NMD), which drives selective destruction of aberrant or physiological mRNAs containing a premature termination codon (9)(10)(11), occurs during the first round of translation driven by the CBC (1). The above view, however, was recently challenged by two reports showing that NMD occurs in the cytoplasm, regardless of whether the CBC or eIF4E drives the first round of translation (12,13).…”
mentioning
confidence: 99%